(untitled) (Journal of Decolonising Disciplines, 2021)
A racial incident revolving around the teaching of To Kill a Mockingbird in a South African school has prompted this examination of how set works are implicated in the dissemination race-related beliefs. The way the book is taught, it is argued, cements the continuation of the alienation of blackness by affirming ubiquitous white normativity. It perpetuates the notion that the fault lies in an ‘existential deviation’ that inheres in black people. This examination highlights how, through the purposive propagation of white normality, the book exhibits anti-black sentiments. The sympathetic white psyche that subsists simultaneously with the continuing enjoyment of racial favouritism, is appraised. The stance of the book is confronted by noting the contrived largely absent voices of black people in the narrative. This book positions the black characters as props, for the absolution of the white protagonists (and by proxy sympathetic white people) during circumstances of the unremitting and deadly racial oppression.